2012
DOI: 10.5539/elt.v5n3p178
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Teachers in Reducing/Increasing Listening Comprehension Test Anxiety: A Case of Iranian EFL Learners

Abstract: Three components have been introduced for foreign language learning anxiety in the literature: Test anxiety, fear of negative evaluation and communication apprehension. This study teases out the first of the three components with special focus on listening comprehension test to investigate the correlation between listening test results and foreign language anxiety. More importantly, the study aims at questioning the role teachers can play in either alleviating or aggravating the anxiety which has been triggere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 24 publications
5
18
1
2
Order By: Relevance
“…The result supports the findings from previous studies which investigated the correlation between foreign language class anxiety and learners' listening performance (Baily, 1983;Aida, 1994;Cheng et al, 1999;Horwitz et al, 1986;MacIntyre & Gardner, 1991;Phillips, 1992;Saito et al, 1999;Sellers, 2000;Sadighi, et al, 2009 andAtasheneh &Izadi 2012). …”
Section: Discussionsupporting
confidence: 82%
“…The result supports the findings from previous studies which investigated the correlation between foreign language class anxiety and learners' listening performance (Baily, 1983;Aida, 1994;Cheng et al, 1999;Horwitz et al, 1986;MacIntyre & Gardner, 1991;Phillips, 1992;Saito et al, 1999;Sellers, 2000;Sadighi, et al, 2009 andAtasheneh &Izadi 2012). …”
Section: Discussionsupporting
confidence: 82%
“…The operational definition of language classroom anxiety and the questions on the LAMS measuring the construct were adopted from Gardner's original study (1985), and measure a participant'sdegree of comfort or discomfort while participating in language class activities. The results from the current study supports research connecting language classroom anxiety to EFL student performance on oral language assessments (Atasheneh & Izadi, 2012;Hewitt & Stephenson, 2012).…”
Section: Understanding Relationships Between Learner Attributes and Lsupporting
confidence: 79%
“…Research has demonstrated that foreign language teachers can reduce student anxiety through interventions that help them build confidence (Atasheneh & Izadi, 2012), and that exposing learners to the kinds of communicative tasks and the expectations to be met in those tasks throughout curriculum implementation can lower the anxiety levels of learners in testing situations (Gorsuch, 2009). This would suggest that curriculum implementation incorporate repeated opportunities for learners to engage in the kinds of communicative tasks reflected in assessments used to measure learner outcomes.…”
Section: Understanding Relationships Between Learner Attributes and Lmentioning
confidence: 99%
“…The state has classically been described by Charles Spielberger (1983, 1) as 'the subjective feeling of tension, apprehension, nervousness, and worry associated with an arousal of the autonomic nervous system.' Multiple studies have shown that the level of anxiety is negatively tied to academic success and can well predict students' academic abilities ( Alrabai, 2014;Anyadubalu, 2010;Atasheneh and Izadi, 2012;Batumlu and Erden, 2007;Hewitt and Stephenson, 2011;Horwitz, 2001;Mahmood and Iqbal, 2010;Wilson, 2006). In Gallagher's (2012) National Survey of College Counseling, college students have ranked anxiety as a major factor for their low academic achievement.…”
Section: International Journal Of Languages' Education and Teachingmentioning
confidence: 99%